Indomethacin Treatment Post-irradiation Improves Mouse Parotid Salivary Gland Function via Modulation of Prostaglandin E2 Signaling - Gilman, Kristy E.; Camden, Jean M.; Woods, Lucas T.; Weisman, Gary A.; Limesand, Kirsten H. (Frontiers in Bioengineering and Biotechnology, 2021)
Annually, >600,000 new cases of head and neck cancer (HNC) are diagnosed worldwide with primary treatment being surgery and radiotherapy. During ionizing radiation (IR) treatment of HNC, healthy salivary glands are collaterally damaged, leading to loss of function that severely diminishes the quality of life for patients due to increased health complications, including oral infections and sores, cavities, and malnutrition, among others. Therapies for salivary hypofunction are ineffective and largely palliative, indicating a need for further research to uncover effective approaches to prevent or restore loss of salivary gland function following radiotherapy. Previous work in our lab implicated prostaglandin E2 (PGE2) as an inflammatory mediator whose release from radiation-exposed cells promotes salivary gland damage and loss of function. Deletion of the P2X7 purinergic receptor for extracellular ATP reduces PGE2 secretion in irradiated primary parotid gland cells, and salivary gland function is enhanced in irradiated P2X7R-/- mice compared to wildtype mice. However, the role of PGE2 signaling in irradiated salivary glands is unclear and understanding the mechanism of PGE2 action is a goal of this study. Results show that treatment of irradiated mice with the nonsteroidal anti-inflammatory drug indomethacin, which reduces PGE2 production via inhibition of cyclooxygenase-1, improves salivary gland function compared to irradiated vehicle-treated mice. To define the signaling pathway whereby PGE2 induces salivary gland dysfunction, primary parotid gland cells treated with PGE2 have increased c-Jun N-terminal Kinase (JNK) activation and cell proliferation and reduced amylase levels and store-operated calcium entry. The in vivo effects of blocking PGE2 production were also examined and irradiated mice receiving indomethacin injections have reduced JNK activity at 8 days post-irradiation and reduced proliferation and increased amylase levels at day 30, as compared to irradiated mice without indomethacin. Combined, these data suggest a mechanism whereby irradiation-induced PGE2 signaling to JNK blocks critical steps in saliva secretion manifested by a decrease in the quality (diminished amylase) and quantity (loss of calcium channel activity) of saliva, that can be restored with indomethacin. These findings encourage further attempts evaluating indomethacin as a viable therapeutic option to prevent damage to salivary glands caused by irradiation of HNC in humans.